Confirmatory Factor Analysis (CFA) of School Capacity Barriers in the Teaching Process in Elementary Schools - Muh. Asharif Suleman; Hilmi, Ahmad (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The purpose of this study is to determine the factors that hinder school capacity in teaching. This study uses a quantitative approach to determine the factors that determine the Barriers to Teaching in Schools. The data analysis method in this study is confirmatory factor analysis (CFA). The data of this study were processed using the JASP program (Jeffrey's Amazing Statistics Program). The type of data collected was the results of PISA 2018. This study used primary data with a number of respondents of 50 schools. The results show that the fit of all models is acceptable. It can be concluded that P1, P2, Q1, and Q2 are the barriers to school capacity for teaching.